The relationship between multiple traumatic events and the severity of posttraumatic stress disorder symptoms – evidence for a cognitive link. Issue 1 (31st December 2023) - Kube, Tobias; Elssner, Anna Caroline; Herzog, Philipp
ABSTRACT: Background: Previous research has shown that multiple traumatic experiences cumulatively increase the risk for the development of severe symptoms of posttraumatic stress disorder (PTSD). Yet, little is known about the specific psychological mechanism through which this increased risk comes about. Objective: In the present study, we examined a possible cognitive link between multiple traumatic events and PTSD symptom severity through dysfunctional cognitions and expectations. Methods: A sample of patients with a diagnosed PTSD ( N  = 70; M Age  = 42.06; 82% female) and high symptom burden (IES-R M  = 79.24) was examined. On average, patients had experienced 5.31 different traumatic events. In a structural equation model, we tested the hypothesis that the relationship between multiple traumatic experiences and PTSD symptom severity is mediated through dysfunctional general cognitions and dysfunctional situation-specific expectations. General trauma-related cognitions were assessed with the Posttraumatic Cognition Inventory (PTCI) and trauma-related situational expectations were assessed with the Posttraumatic Expectations Scale (PTES). Results: The direct effect of the number of traumatic events on PTSD symptom severity was non-significant. Instead, as hypothesised, there was evidence for a significant indirect effect via dysfunctional general cognitions and situation-specific expectations. Conclusions: The current results further specify the cognitive model of PTSD by indicating that the relationship between the number of traumatic events and PTSD symptom severity is mediated through dysfunctional cognitions and expectations. These findings emphasise the importance of focused cognitive treatment approaches that seek to modify dysfunctional cognitions and expectations in people with multiple traumatic experiences. HIGHLIGHTS: This study shows a cognitive link between the experience of multiple traumatic events and the severity of posttraumatic stress disorder (PTSD) symptoms. The aforementioned relationship is mediated through trauma-related general cognitions and situational expectations. The results provide further evidence for the cognitive model of PTSD and further specify it by considering different types of trauma-related cognitions.